Moema humaita, a new species of annual fish (Cyprinodontiformes: Rivulidae) from the middle rio Madeira, Amazon basin, Brazil - Nielsen, Dalton Tavares Bressane; Hoetmer, Jan Willem; Vandekerckhove, Eric (Zootaxa, 2025)
Moema humaita, new species, is described from a seasonal pool in the rio Madeira drainage, Amazon River basin, Brazil. The new species is assigned to the Moema staecki species group based on the color pattern in males, composed of dots following interrupted lines arranged horizontally. Moema humaita differs from all known congeners by its unique color pattern in males, presenting body sides light grey, with three horizontal lines, composed by small red dots lying in the center of each scale, alternating with three bright yellow lines, and additionally by presenting caudal fin with 3–4 long filamentous rays and presenting an anal fin long, with its tip pointed, reaching vertical through near the end of the caudal fin, orange in color. The occurrence of an undescribed species of the genus Moema in Guyana is reported based on a photograph of an unpreserved specimen.